A Review of Deep Learning Techniques on Fundus Images for Detecting Diabetic Retinopathy on Public Datasets - Kumar, Silpa Ajith; Kumar, J. Satheesh; Neraniki, Preethi; Yadav, Kothagorla Asritha; Basha, Shaik Shaheer (Journal of Innovative Image Processing, 2022)
The primary source of vision loss in patients is mainly due to Diabetic retinopathy (DR), caused due to diabetes mellitus. It has become a significant reason for visual impairment among people within 25-74 years of age. If timely medical attention is provided to DR patients, over 90% of people can be saved from vision loss. It's crucial for the early diagnosis of the disease and provide the necessary treatment. The symptoms are more prevalent in type 2 diabetics than associated with type 1 diabetics. Unlike computer-aided diagnosis systems, the traditional procedures of DR detection using fundus photography are both time and cost-consuming. Among the numerous methods for screening and detecting DR, Convolutional Neural Networks are considered extensively in Deep Learning (DL) methods. This review article illustrates the different datasets, pre-processing steps, and DL techniques used in the fundus images for efficient DR detection at an early stage. The main motive of this review article is to provide the research community with an insight into the various pre-processing steps, Public datasets, DL models in DR detection, and some future research directions in this field.
Keywords: Convolution Neural Networks (CNNs); Deep Learning (DL); Diabetic Macular Edema (DME); Diabetic Retinopathy (DR); Fundus Images